The armed forces role in emergencies in Brazil: a case of conservative securitization - da Gama Janot, Mariana [UNESP]; Succi, David Paulo [UNESP]; Soares, Samuel Alves [UNESP] (Escuela Militar de Cadetes Jose Maria Cordova, 2024)
In this article, we analyze the role of the Brazilian armed forces in emergencies based on discussions about the securitization of development and militarization. We argue that the military response to emergencies is a process strongly characterized by the conservative history of the organization, assimilating humanitarian actions and activities directed at the population within conceptions of the use of force concerned with internal order. We analyze contemporary legislation and the Army's doctrinal production on civic-social activities, support for civil defense, and disaster assistance. We consider this to be a sui generis process of militarization in the context of military action in emergencies because although certain climatic events are less common in Brazil, we observe that these activities have been part of a broader set of militarization in the country.
El papel de las fuerzas armadas en situaciones de emergencia en Brasil: un caso de securitización conservadora
Keywords: armed forces; Brazil; disaster relief; militarism; militarization; securitization